2019
DOI: 10.3390/su11205810
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Effects of Student and School Factors on Senior High School Students’ Ocean Literacy

Abstract: This study explored the variance in ocean literacy accounted for by student and school levels and examined the influence of these two predictors on senior high school students’ ocean literacy using a hierarchical linear model. Data were collected from 1944 students from 99 schools and used to construct the two-level hierarchical linear model. The results indicated that the variance in ocean literacy accounted for by students was larger than that accounted for by schools; approximately a quarter of the total va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Students' sources of ocean knowledge indicated that mass communication channels are crucial for them to acquire ocean knowledge. International surveys on the sources of ocean literacy have revealed that popular science sources (e.g., reading magazines and books) and media applications (e.g., television media and online education) are key factors in enhancing students' ocean knowledge and literacy [18,62].…”
Section: Middle School Students' Ocean Knowledge Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…Students' sources of ocean knowledge indicated that mass communication channels are crucial for them to acquire ocean knowledge. International surveys on the sources of ocean literacy have revealed that popular science sources (e.g., reading magazines and books) and media applications (e.g., television media and online education) are key factors in enhancing students' ocean knowledge and literacy [18,62].…”
Section: Middle School Students' Ocean Knowledge Sourcesmentioning
confidence: 99%
“…Therefore, students from coastal schools had significantly higher degrees of ocean literacy than did noncoastal schools [44]. The results of a study in which Taiwanese scholars constructed an ocean literacy scale for high school students revealed that school location is a key factor [13,18]. However, this result differed from that of a US survey on Virginian students [23].…”
Section: Influence Of Background Variables On Middle School Students'mentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, the protection of the ocean has become one of the most urgent issues in the world environmental agenda. Several studies on marine education and related topics have been addressed by numerous surveys carried out among students (Lin et al 2020;Tsai 2019;Guest, Lotze, and Wallace 2015;Plankis and Marrero 2012) and teachers (Hartley et al 2018;Dromgool-Regan, Burke, and McClouglin 2017). The literature has revealed a knowledge gap about ocean science-related topics in several countries (Winks et al 2020;Ankamah-Yeboah et al 2020;Fauville et al 2019;Leitão et al 2018;Costa and Caldeira 2018;Papathanassiou et al 2017;Guest, Lotze, and Wallace 2015;Corner, Capstick, and Pidgeon 2014).…”
Section: Introductionmentioning
confidence: 99%